2017
DOI: 10.1038/s41598-017-17822-z
|View full text |Cite
|
Sign up to set email alerts
|

First demonstration of coherent Cherenkov radiation matched to circular plane wave

Abstract: We observed coherent Cherenkov radiation matched to a circular plane wave (CCR-MCP) for the first time using a hollow conical dielectric made of a high-density polyethylene. The refractive index and the absorption coefficient of the dielectric were evaluated to be 1.537 ± 0.004 and 0.006 ± 0.028 by measuring the pulse formed by the interference between the CCR-MCP and the coherent diffraction radiation. These values were consistent with the values shown in a reference for the high-density polyethylene. In acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The teflon Cherenkov cone was cut in such a way to build a forward plane-wave of radiation, copropagating with the beam towards the mirror. A significant enhancement of about a factor 3 higher in photon yield with respect to a CTR/CDR radiator was observed at a radiatormirror distance of about 40 cm as well as a slight shift towards a higher peak frequency (proper of the Cherenkov mechanism itself), consistent with the observations in [43]. An average power of about half mW, peaked at 60 GHz with a relative bandwidth of 100% was obtained finally.…”
Section: Comparison Among Different Radiation Mechanismssupporting
confidence: 85%
“…The teflon Cherenkov cone was cut in such a way to build a forward plane-wave of radiation, copropagating with the beam towards the mirror. A significant enhancement of about a factor 3 higher in photon yield with respect to a CTR/CDR radiator was observed at a radiatormirror distance of about 40 cm as well as a slight shift towards a higher peak frequency (proper of the Cherenkov mechanism itself), consistent with the observations in [43]. An average power of about half mW, peaked at 60 GHz with a relative bandwidth of 100% was obtained finally.…”
Section: Comparison Among Different Radiation Mechanismssupporting
confidence: 85%
“…formed with an L-band electron linac at KURNS-LINAC. Various types of coherent radiations have been studied in this facility [31][32][33][34] , and a THz-band beamline that can supply coherent transition radiation for spectroscopic experiments has been constructed 35 . Because a large diffractor assembly with a volume of 10 cm 3 or more can be installed in the aluminium vacuum chamber which is used for generation of the coherent transition radiation, the CBDR can generate at frequencies less than 0.1 THz.…”
Section: Experimental Setup At Kurns-linac the Demonstration Experimmentioning
confidence: 99%
“…Radiation of charged particles moving in the presence of dielectric objects ("targets") is of vital interest for various applications [1][2][3][4][5]. For example, several experiments have shown that prismatic and conical targets can be prospective for both bunch diagnostics and generation of high-power radiation [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation of charged particles moving in the presence of dielectric objects ("targets") is of vital interest for various applications [1][2][3][4][5]. For example, several experiments have shown that prismatic and conical targets can be prospective for both bunch diagnostics and generation of high-power radiation [2][3][4][5]. Further development of these topics requires an accurate calculation of Cherenkov radiation (CR) outside dielectric objects, which is typically impossible to do rigorously due to the complicated geometry of these objects.…”
Section: Introductionmentioning
confidence: 99%